STRONG COUPLING LIMITS and QUANTUM ISOMORPHISMS of THE GAUGED THIRRING MODEL - Bufalo, R. [UNESP]; Casana, R.; Pimentel, B. M. [UNESP] (World Scientific Publ Co Pte Ltd, 2011)
We have studied the quantum equivalence in the respective strong coupling limits of the bidimensional gauged Thirring model with both Schwinger and Thirring models. It is achieved following a nonperturbative quantization of the gauged Mining model into the path-integral approach. First, we have established the constraint structure via the Dirac's formalism for constrained systems and defined the correct vacuum-vacuum transition amplitude by using the Faddeev-Senjanovic method. Next, we have computed exactly the relevant Green's functions and shown the Ward-Takahashi identities. Afterwards, we have established the quantum isomorphisms between gauged Thirring model and both Schwinger and Thirring models by analyzing the respective Green's fund ions in the strong coupling limits, respectively. A special attention is necessary to establish the quantum isomorphism between the gauged Thirring model and the Thirring model.
Keywords: Bidimensional models; nonperturbative methods; strong coupling limits